2013
DOI: 10.1002/psp.1829
|View full text |Cite
|
Sign up to set email alerts
|

Lonely Sunsets: Impacts of Rural–urban Migration on the Left‐behind Elderly in Rural China

Abstract: Drawing on the data from the research that samples 400 elderly who lived separately from their migrant children in 10 rural communities in China, this paper examines how the outmigration of rural youth shapes the situation of their older kin and analyses the consequences of the rural–urban migration for the old‐age support system. The research finds that a large scale of rural labour force has been drained off from rural societies and placed in a ‘semi‐proletarianized’ situation during the recent three decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 17 publications
0
82
1
Order By: Relevance
“…Future research should include more detailed information on the reasons for migration in each household (ie, push or pull factors) which seem to affect the impact of outmigration on the psychological health of those left behind. In this study, neither household size, which has been shown to be one of the key components of family support in China (Zimmer & Kwong, 2003) nor contacts with migrants via telephone calls, which was suggested to be an essential way to maintain emotional connections (He & Ye, 2014), was associated with EBV antibody titers among those left behind; that is, they did not mitigate the stress of being left behind.…”
Section: F I G U R E 1 Predicted Epstein-barr Virus Antibody Titers Incontrasting
confidence: 56%
“…Future research should include more detailed information on the reasons for migration in each household (ie, push or pull factors) which seem to affect the impact of outmigration on the psychological health of those left behind. In this study, neither household size, which has been shown to be one of the key components of family support in China (Zimmer & Kwong, 2003) nor contacts with migrants via telephone calls, which was suggested to be an essential way to maintain emotional connections (He & Ye, 2014), was associated with EBV antibody titers among those left behind; that is, they did not mitigate the stress of being left behind.…”
Section: F I G U R E 1 Predicted Epstein-barr Virus Antibody Titers Incontrasting
confidence: 56%
“…In addition, the study included more female subjects, which could also contribute to the selection bias. It has been reported that rural elderly women experienced greater social isolation and mental health issues compared to their urban counterparts, 49 which may affect the study results. On the other hand, the intervention provided by the original RCT appeared to be feasible and effective to improve SM behaviors and address SM needs in this vulnerable and high risk population.…”
Section: Discussionmentioning
confidence: 96%
“…The higher the income and the medical condition, the better their health condition [38]. As some researchers point out, children's migration contributes to the material well-being of their parents and better economic status is associated with less adverse health outcomes [7,39]. Some studies also show that heavy living burden and shortage of available medical service resources lead to higher incidence of stroke and heart disease for the left behind elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also show that heavy living burden and shortage of available medical service resources lead to higher incidence of stroke and heart disease for the left behind elderly. Also, when negative emotions such as loneliness increase, the mental health and self-rated health status reduce [21,39]. The three-level indicator with the largest weight value is the assistance provided by medical institutions.…”
Section: Discussionmentioning
confidence: 99%